1.5 µm high-energy burst-mode picosecond pulsed lasers based on an optical parametric oscillator. (23rd August 2018) - He, Li-Jiao; Liu, Ke; Liu, Zhao; Bo, Yong; Wang, Xiao-Jun; Yuan, Lei; Zong, Qing-Shuang; Peng, Qin-Jun; Cui, Da-Fu; Xu, Zu-Yan
Abstract: A high-energy burst-mode picosecond pulsed laser at 1.5 µ m was demonstrated based on an optical parametric oscillator. When the pulse repetition rate of the burst was set at 10 and 20 kHz respectively, both the temporal duration of the pulse-burst and the number of individual picosecond pulses in each burst continuously increase with an increase in absorbed pump power. Under an absorbed pump power of 12.7 W, a maximum burst energy of 50.5 µ J was achieved at a repetition of 10 kHz, and the burst pulse duration was 320 ns with 31 individual picosecond pulses per burst. Also, for a repetition rate of 20 kHz, the burst pulse duration was 260 ns containing 25 individual picosecond pulses with a burst energy of 21.4 µ J. The individual pulse width underneath the burst was about 7.8 ps. The beam quality factor was measured to be M 2   =  1.74 at 10 kHz under a maximum absorbed pump power of 12.7 W. Such a burst-mode picosecond laser is important for material processing.